Instability analysis of a deep tunnel under triaxial loads using a three-dimensional numerical method with strength reduction method. (April 2019) - Liang, Zhengzhao; Gong, Bin; Li, Wanrun
Abstract: Influence of triaxial stress states on failure behaviors and safety factor of deep tunnels, involving the intermediate principal stress and the ratio of the vertical stress to the horizontal stress, is investigated using a three-dimensional numerical model and the strength reduction method (SRM). The numerical model is able to consider the heterogeneity of rock masses described by the Weibull distribution based on the statistical damage theory. The strength reduction method is applied to implement the progressive failure modelling of the surrounding rocks, and the tunnel stability under different stress conditions is obtained. The results show that the failure behaviors of the surrounding rocks are complex under the effect of triaxial stress states. Both the lateral pressure coefficient and axial stress have significant influence on the tunnel failure patterns. When the direction of the intermediate principal stress is parallel to the tunnel axis, the safety factor of the tunnels increases with the increasing of the intermediate principal stress. When the direction of the intermediate principal stress is perpendicular to the tunnel axis, the safety factor increases in the beginning and then decreases as the intermediate principal stress increases gradually until reaching the maximal principal stress. When the direction of the maximum principal stress is parallel to the tunnel axis, the zonal disintegration is observed because of the large axial stress. Overall, the numerical model is successfully adopted to model the fracture patterns and evaluate the tunnel stability. The simulated results have contributed to reveal the nonlinear failure behaviors of deep tunnels and understand their safety condition under complex triaxial stress states.